Parity and Components of the Metabolic Syndrome Among US Hispanic/Latina Women: Results From the Hispanic Community Health Study/Study of Latinos. (February 2016) - Vladutiu, Catherine J.; Siega-Riz, Anna Maria; Sotres-Alvarez, Daniela; Stuebe, Alison M.; Ni, Andy; Tabb, Karen M.; Gallo, Linda C.; Potter, JoNell E.; Heiss, Gerardo
Abstract : Background—: Physiological adaptations occurring across successive pregnancies may increase the risk of adverse cardiovascular health outcomes in later life. Methods and Results—: The association between parity and metabolic syndrome was examined among 7467 Hispanic/Latina women of diverse backgrounds, aged 18 to 74 years, who participated in the Hispanic Community Health Study/Study of Latinos (HCHS/SOL) from 2008 to 2011. Metabolic syndrome components were defined according to American Heart Association/National Heart, Lung, and Blood Institute criteria and included abdominal obesity, elevated triglycerides, low high-density lipoprotein cholesterol, high blood pressure, and elevated fasting glucose. Logistic regression models estimated odds ratios (ORs) adjusting for sociodemographic, behavioral, and reproductive characteristics. At HCHS/SOL baseline, women reported none (21.1%), 1 (19.9%), 2 (25.7%), 3 (18.6%), 4 (8.8%), and ≥5 (5.9%) live births. When compared with women with 1 birth, those with 4 births had the highest odds of abdominal obesity (OR, 2.0; 95% confidence interval, 1.5–2.8) and overall metabolic syndrome (OR, 1.4; 95% confidence interval, 1.0–2.0) and those with ≥5 births had the highest odds of low high-density lipoprotein cholesterol (OR, 1.5; 95% confidence interval, 1.2–2.0) and elevated fasting glucose (OR, 1.6; 95% confidence interval, 1.1–2.4), after adjusting for age, background, education, marital status, income, nativity, smoking, physical activity, menopause, oral contraceptive use, hormone therapy, and field center. Further adjustment for percent body fat attenuated these associations. No associations were observed between parity and elevated triglycerides or high blood pressure. Conclusions—: Higher parity is associated with an increased prevalence of selected components of the metabolic syndrome among Hispanic/Latina women in the US. High parity among Hispanics/Latinas with a high prevalence of abdominal obesity suggests high risk for metabolic dysregulation. Abstract : Supplemental Digital Content is available in the text.